2008
DOI: 10.1254/jphs.fm0070109
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Clinical Aspects of Non-neuronal Acetylcholine: Expression of an Independent, Non-neuronal Cholinergic System in Lymphocytes and Its Clinical Significance in Immunotherapy

Abstract: Abstract. Lymphocytes possess all the components required to constitute an independent, non-neuronal cholinergic system. These include acetylcholine (ACh); choline acetyltransferase (ChAT), its synthesizing enzyme; and both muscarinic and nicotinic ACh receptors (mAChRs and nAChRs, respectively). ACh modifies T and B cell function via both mAChR-and nAChRmediated pathways. Stimulation of lymphocytes with the T cell activator phytohemagglutinin, protein kinase C activator phorbol ester, or cell surface molecule… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
83
1
5

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 106 publications
(92 citation statements)
references
References 36 publications
3
83
1
5
Order By: Relevance
“…30 The factors that can affect both the repertoire and the ligandbinding affinities of cholinergic receptors include the dose and duration of exposure to an agonist, antigen stimulation, cytokine milieu and a large variety of other non-immunological and immunological stimulations. [2][3][4]10,22,[31][32][33][34][35][36][37][38] This helps in explaining the discrepancy of our in vitro findings with the previous report that nicotine treatment of mice with experimental autoimmune encephalomyelitis fosters a shift from Th1 toward Th2 or Th3 responses. 38 In that study, however, the reduction in secreted IFN-g was most marked in CD8 compared with CD4 cells.…”
Section: Cholinergic Receptors Of Murine T Cells J Qian Et Almentioning
confidence: 58%
See 3 more Smart Citations
“…30 The factors that can affect both the repertoire and the ligandbinding affinities of cholinergic receptors include the dose and duration of exposure to an agonist, antigen stimulation, cytokine milieu and a large variety of other non-immunological and immunological stimulations. [2][3][4]10,22,[31][32][33][34][35][36][37][38] This helps in explaining the discrepancy of our in vitro findings with the previous report that nicotine treatment of mice with experimental autoimmune encephalomyelitis fosters a shift from Th1 toward Th2 or Th3 responses. 38 In that study, however, the reduction in secreted IFN-g was most marked in CD8 compared with CD4 cells.…”
Section: Cholinergic Receptors Of Murine T Cells J Qian Et Almentioning
confidence: 58%
“…[3][4][5][6] It has been demonstrated that the immunological activation of lymphocytes evokes cholinergic signal transmission between T cells and target cells by enhancing synthesis and release of ACh and modifying the expression of ACh receptors (reviewed in ref. 2). T cells produce more ACh than B cells, and CD4 cells more than CD8 cells.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…ACh can stimulate five different G-protein-coupled muscarinic receptor subtypes (CHRMs, also known as mAChR ;Nathanson 2008) and an unknown variety of ionotropic nicotinic ACh receptors (CHRN; also known as nAChR) with subtype-specific arrangements of nine a-and four b-subunits in mammals (Albuquerque et al 2009). It is now known that the cholinergic system, traditionally associated with neurotransmission, is not restricted to neurons but plays an important role in the structure and function of non-neuronal tissues such as epithelia and the immune system (Fujii et al 2008, Kummer et al 2008, Wessler & Kirkpatrick 2008. For example, in epithelia, CHRNs are involved both in maintaining the integrity of the epithelial layer and in the development of neoplastic changes (Grando et al 2003, Grozio et al 2007, Paleari et al 2009).…”
Section: Introductionmentioning
confidence: 99%